Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) in the Brain and Relevance for Neuropsychiatric Disorders - O’Connell, Emma M.; Lohoff, Falk W. (Frontiers in Neuroscience, 2020)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) has long been studied in the liver due to its regulation of plasma low-density lipoprotein cholesterol (LDL-C) and its causal role in familial hypercholesterolemia. Although PCSK9 was first discovered in cerebellar neurons undergoing apoptosis, its function in the central nervous system is less clear. PCSK9 has been shown to be involved in neuronal differentiation, LDL receptor family metabolism, apoptosis and inflammation in the brain, but in vitro and in vivo studies offer contradictory findings. PCSK9 expression in the adult brain is low but is highly upregulated during disease states. Cerebral spinal fluid (CSF) PCSK9 concentrations are correlated with neural tube defects and neurodegenerative diseases in human patients. Epigenetic studies reveal that chronic alcohol use may modulate methylation of the PCSK9 gene and genetic studies show that patients with gain-of-function PCSK9 variants have higher LDL-C and an increased risk of ischemic stroke. Early safety studies of the PCSK9 inhibitors evolocumab and alirocumab, used to treat hypercholesterolemia, hinted that PCSK9 inhibition may negatively impact cognition but more recent, longer-term clinical trials found no adverse neurocognitive events. The purpose of this review is to elucidate the role of PCSK9 in the brain, particularly its role in disease pathogenesis.